Functionalized Nanoparticles in Prevention and Targeted Therapy of Viral Diseases With Neurotropism Properties, Special Insight on COVID-19 - Ren, Meishen; Wang, Yin; Luo, Yan; Yao, Xueping; Yang, Zexiao; Zhang, Pengfei; Zhao, Wei; Jiang, Dike (Frontiers in Microbiology, 2021)
Neurotropic viruses have neural-invasive and neurovirulent properties to damage the central nervous system (CNS), leading to humans’ fatal symptoms. Neurotropic viruses comprise a lot of viruses, such as Zika virus (ZIKV), herpes simplex virus (HSV), rabies virus (RABV), and severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2). Effective therapy is needed to prevent infection by these viruses in vivo and in vitro. However, the blood-brain barrier (BBB) usually prevents macromolecules from entering the CNS, which challenges the usage of the traditional probes, antiviral drugs, or neutralizing antibodies in the CNS. Functionalized nanoparticles (NPs) have been increasingly reported in the targeted therapy of neurotropic viruses due to their sensitivity and targeting characteristics. Therefore, the present review outlines efficient functionalized NPs to further understand the recent trends, challenges, and prospects of these materials.